Snow angel cove eaudiobook Haven point series, book 1. - Thayne, RaeAnne (Haven Point, 2014)
New York Times bestselling author RaeAnne Thayne welcomes you to a small town full of big surprises that are both merry and bright... Nothing short of a miracle can restore Eliza Hayward's Christmas cheer. The job she pinned her dreams on has gone up in smoke-literally-and now she's stuck in an unfamiliar, if breathtaking, small town. Precariously close to being destitute, Eliza needs a helping hand.for her sick young daughter's sake as well as her own. But she's not expecting her holiday hero to almost run her down with his car! Rescuing Eliza is pure instinct for tech genius Aidan Caine. At first, putting the renovation of his lakeside guest lodge in Eliza's hands assuages his guilt-until he sees how quickly he could fall for her. Having focused solely on his business for years, he never knew that what his life was missing was Eliza and her little girl. But is he willing to risk hoping for a yuletide romance that could lead to forever?